Unethical employee behavior against coworkers following unkind management treatment: An experimental analysis - Sabrina Jeworrek; Joschka Waibel (Managerial and Decision Economics, 2021)
We study unethical behavior toward unrelated coworkers as a response to managerial unkindness with two experiments. In our lab experiment, we do not find that subjects who experienced unkindness are more likely to cheat in a subsequent competition against another coworker who simultaneously experienced mistreatment. A subsequent survey experiment suggests that behavior in the lab can be explained by individuals' preferences for norm adherence, because unkind management behavior does not alter the perceived moral appropriateness of cheating. However, having no shared experience of managerial unkindness opens up some moral wiggle room for employees to misbehave at the costs of others.
Keywords: 650